2018
DOI: 10.15395/mkb.v50n3.1368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Intensity Exercise on Body Weight and Blood Estrogen Level Ovariectomized Mice

Abstract: Estrogen is a hormone which is related to lipid oxidation, lypogenesis inhibition, and lipolysis rate. The purpose of this study was to determine the effect of moderate intensity exercise on body weight and blood estrogen level in ovarectomized mice (ovx). The study was held in the Laboratory of Biochemistry, Faculty of Medicine Universitas Airlangga during the period of April to May 2017 on old nineteen 3-4 months old female mice, , 20-30 grams of weight, which were divided into two groups: OVX (n=9, ovx with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The One-Way ANOVA test results show that there was no significant difference in the average pre-exercise body weight in all groups, while 4 weeks post-exercise and delta ( ) showed a significant difference in the average body weight in all groups (Table 1). These results are in line with the research from Prasetya et al (2018), which reported that Moderate-Intensity Exercise (MIE) for 4 weeks reduced body weight in mice.Likewise research conducted by Houdebine et al (2019), which reported that swimming training significantly reduced body weight compared to the control group. Inoue et al (2015) in their research reported that mild exercise (ME) and intense exercise (IE) significantly reduced body weight compared to controls (CONT).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The One-Way ANOVA test results show that there was no significant difference in the average pre-exercise body weight in all groups, while 4 weeks post-exercise and delta ( ) showed a significant difference in the average body weight in all groups (Table 1). These results are in line with the research from Prasetya et al (2018), which reported that Moderate-Intensity Exercise (MIE) for 4 weeks reduced body weight in mice.Likewise research conducted by Houdebine et al (2019), which reported that swimming training significantly reduced body weight compared to the control group. Inoue et al (2015) in their research reported that mild exercise (ME) and intense exercise (IE) significantly reduced body weight compared to controls (CONT).…”
Section: Discussionsupporting
confidence: 91%
“…Swimming exercises were carried out 3 times in a week for 4 weeks with an intensity of 6% of body weight and the duration was 70% of maximum time (Prasetya et al, 2018). Morning swimming exercise was held at 08.00-09.00 AM, while night swimming exercise was held at 20.00-21.00 PM (Pranoto et al, 2020;Kwak et al, 2020).…”
Section: Protocol Of Exercisementioning
confidence: 99%
“…Calorie restriction is done 3x/ week at night and a high-calorie ed libitium diet and Sonde D40 at noon 7 times/week for 4 weeks. The moderate-intensity continuous exercise was carried out by immersing the mice with a load of 6% of the bodyweight of the mice tied to the tail rank 35 for 15 minutes 36 . Swimming training interventions were given 3 times/week for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The control group received standard diet, while the high-calorie diet group was given ad libitum with dextrose (D40) using sonde in a dose of 3-5% of calories or 0.0325 mL/gBW every day (Herawati et al 2020). The combination group of high-calorie diet and moderate-intensity physical exercise received the same diet with K2 group plus swimming three times a week (Monday, Wednesday, Friday) for 15 minutes using 6% of the mice's body weight loading (Prasetya et al 2018;Zhao et al 2018). The swimming intervention was carried out in the water with a temperature of 25±1°C inside a tub with a height of 60 cm and diameter of 50 cm.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%